Security Challenges of Modernity: Russian Federation Information Activity on the Backdrop of a Pandemic Covid-19 - Karpo, Vasyl; Nechaieva-Yuriichuk, Nataliia (ANNALES UNIVERSITATIS MARIAE CURIE-SKŁODOWSKA LUBLIN – POLONIA, 2021)
The article is dedicated to the Russian Federation information activity on the backdrop of a pandemic Covid-19
Keywords: Security, Covid-19, Information